A mathematical model for distribution of calcium in silicon by vacuum directional solidification - Zheng, Damin; Wei, Kuixian; Ma, Wenhui; Sheng, Zhilin; Dai, Yongnian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
Calcium is one of the main impurity elements in silicon. It is a key to remove calcium effectively in the process of polycrystalline silicon ingot production by vacuum directional solidification furnace. Based on the consideration of the theory of segregation, mass transfer and evaporation during vacuum directional solidification process, a mathematical model for distribution of calcium in silicon was proposed to reveal the removal mechanism. In order to confirm the mathematical model, UMG-Si with an initial purity of 99.98 wt. % was used in an industrial scale experiment. Moreover, temperature as a manageable parameter influences evaporation and segregation at the same time. For this reason, the dependences of effective segregation coefficient (keff) and the evaporation coefficient (kE) on temperature were carefully investigated. The results show that the mathematical model agrees with the experimental data and calcium removal is mainly determined by evaporation.